Shear band multiplication induced strong strain delocalization and high tensile ductility in amorphous thin films by metallic substrates. (15th June 2020) - Chen, Tianyu; Li, Jianjun; Chen, Shaohua; Li, Chun
Highlights: Tensile deformation of amorphous films on metallic substrates is studied. The effects of film thickness and interface strength are considered. Multiple shear bands are generated in amorphous films by the metallic substrate. Shear band multiplication induces strong strain delocalization and high tensile ductility in amorphous films. Shear band numbers increase with applied strain and decrease with film thickness. Abstract: Metallic glass usually ruptures at a small strain by forming single dominant shear band under tension at room temperature. Experiments have shown that multiple shear bands can be induced in metallic glass film by a ductile metallic substrate, and the ductility of the film can be elevated significantly. However, the mechanism behind remains unsolved. Here we established a computational model to investigate the effect of a Ni substrate on the deformation of a Ni-P amorphous film. The shear band evolution in the film was described by a free volume-based constitutive theory, while the deformation of the Ni substrate was simulated by a dislocation density-based model. The film/substrate interface was modeled by a cohesive zone law. In the simulations, the shear band evolution and the stress in the film can be measured directly, which is difficult to achieve in experiments. Our simulations show that multiple shear bands have been formed in the substrate-supported metallic glass film if the film thickness h f is less than 10 µm. The thinner the film is, the more the shear bands the film has. The number of shear bands can reach as high as 16 as h f is refined down to 2.5 µm. The generation of the multiple shear bands alleviated the strong strain-softening as observed in free standing film, as clearly shown in the stress-strain response of the thin film in the film/substrate system. The suppressed strain-softening induces significantly enhanced tensile ductility in the amorphous film. The tensile ductility of the 2.5 µm-thick film on the Ni substrate can reach as high as 13.3%, which is much higher than that of the corresponding freestanding film, i.e., 3.1%. The proposed computational model has been validated by the coincident stress-strain responses between simulations and experiments. The findings revealed that the enhanced tensile ductility originates from the shear band multiplication-induced strain delocalization in the amorphous film due to the constraint of the metallic substrate. Graphical abstract: Image, graphical abstract